КОНЦЕПТОСФЕРА „КОЛІР” У РОМАНІ АХІЛЛА ТАТІЯ „ЛЕВКІППА І КЛІТОФОНТ” - Chakal (Makar), Inesa (Casa Cărţii de Ştiinţă, 2016)
This article is an attempt to explore the conceptual sphere of „colour” based on the ancient Greek novel by Achilles Tatius (2nd century A.D.). The textual analysis has revealed 14 descriptive adjectives of colour, their semantic relation with nouns and frequency of using them in a text of the novel. Although a number of adjectives that identify colours are small, the author skilfully uses them in the text, creating symbolical pictures of description, which attracts the reader and creates a unique conceptual sphere of „colour” in the novel.
The Conceptual Sphere of “Colour” in the Novel of Achilles Tatius “Leucippe and Clitophon”
Keywords: conceptual sphere; концептосфера; colour meaning word; кольороназва; adjective; прикметник; давньогрецький роман; ancient greek novel; Ахілл Татій; Achilles Tatius